Medicine reconciliation on admission in a paediatric hospital setting. Issue 6 (9th May 2013) - Butler, E; Bourke, C
Abstract : Background: Medication reconciliation is an organisational practice designed to ensure patients' pre-admission medicines are prescribed correctly upon admission to hospital. Multiple sources of information are needed to do this. This is the first study of its kind in Ireland to examine the role of medication reconciliation on admission in a paediatric hospital. Objectives: To quantify the clinical significance of medication reconciliation in children on admission to hospital, to examine the availability and accuracy of different sources of pre-admission medication information and to investigate whether a successful strategy for medication reconciliation could be expanded to provide benefit for the Irish paediatric population. Methods: A prospective observational study included paediatric inpatients admitted to pre-selected general medical wards between April and July 2011. Five different information sources were examined: healthcare record (HCR), patients' own drugs (PODs), the parents, drug kardex, community pharmacy (CP). A pre-admission medication list was subsequently compiled and discrepancies extracted and analysed. The clinical significance of these discrepancies was determined by an expert multidisciplinary panel using the National Coordinating Council for Medication Error Reporting and Prevention (NCCMERP) classification of medication discrepancies. Results: Forty patients were recruited to this study from pre-selected general medical wards over an 18 week period. Fifteen patients (37.5%) had at least one undocumented discrepancy on their drug kardex. Those patients on greater than four medicines and antiepileptic drug use were associated with a greater proportion of errors. Parents were the best source of medication history information (82.5%) followed by the drug kardex (65%), the CP (45%), the HCR (30%) and the patient's own drugs (20%) respectively. Conclusions: The introduction of medication reconciliation in children on admission to hospital has the potential to reduce discomfort and clinical deterioration by reducing unintended medication discrepancies. Patients in Ireland should be encouraged to bring their medicines into hospital with them to facilitate the medication reconciliation. Multiple sources should be consulted when obtaining medication histories.